Intellectual Property Rights Patent - Lakshmana Prabu, Sakthivel; Tnk, Suriyaprakash; Jacob-Lopes, Eduardo; Queiroz Zepka, Leila (IntechOpen, 2020)
This edited volume, Intellectual Property Rights - Patent, is a collection of reviewed and relevant research chapters, offering a comprehensive overview of recent developments in the field of patents and its issues. The book comprises chapters authored by various researchers and edited by experts active in the pharmaceutical research area. All chapters are complete in itself but united under a common research study topic. This publication aims to provide a thorough overview of the latest research efforts on patenting and the related issues for legal experts and the scientific community and open new possible research paths for further novel developments.